Studi Efek Temperatur Terhadap Transisi Curie pada Material Cobalt Ferrite (CoFe2O4) Feromagnetik menggunakan Vampire - Rifqi Ardiyansyah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Cobalt ferrite (CoFe₂O₄) is a ferromagnetic material that has attracted significant attention due to its high magnetocrystalline anisotropy, chemical stability, and potential applications in magnetic storage and spintronic devices. One of the most important magnetic properties of this material is its Curie temperature, which marks the transition from ferromagnetic to paramagnetic behavior. This study aims to investigate the effects of nanoparticle size and temperature on the Curie transition and hysteresis curve characteristics of ferromagnetic CoFe₂O₄ using the Vampire atomistic spin simulation program. Simulations were performed by varying the size of CoFe₂O₄ nanoparticles at 5, 10, 15, and 20 nm over a wide temperature range. The Curie temperature was determined based on the peak magnetic susceptibility, while the hysteresis properties were analyzed through magnetization curves under varying external magnetic fields at temperatures of 0 K, 300 K, 600 K, and 900 K. Parameters such as coercivity, saturation magnetization, and remanent magnetization were evaluated to classify the material as hard or soft magnet. The results show that the Curie temperature increases with increasing nanoparticle size, where the smallest size (5 nm) exhibits a lower Curie temperature due to dominant surface effects, while larger nanoparticles exhibit more stable ferromagnetic behavior closer to bulk characteristics. Hysteresis analysis shows that CoFe₂O₄ exhibits hard magnetic behavior with high coercivity values, which decrease significantly with increasing temperature due to thermal spin agitation. Overall, this study confirms that nanoparticle size and temperature play an important role in determining the magnetic properties of CoFe₂O₄, and Vampire simulations provide a reliable approach for studying magnetic phase transitions at the nanoscale.
FINALISASI oleh Arif 2026 Mei 12
Keywords: cobalt ferrite; temperatur curie; hysteresis curve; nanoparticle size